Transcriptome sequencing revealed the regulation of stem internode length associated with mechanical harvesting in three tea varieties - Mi, Xiaozeng; Qiao, Dahe; Yang, Chun; Chen, Juan; Liang, Sihui; Guo, Yan (Frontiers in Plant Science, 2025)
IntroductionInternode length of tea plant is one of the key traits affecting the mechanical harvesting effect, but there are relatively few reports on their molecular regulatory.MethodsTranscriptome sequencing (RNA-seq) was performed on it in order to explain its molecular mechanism. GO, KEGG enrichment and WGCNA were used to identify key genes, and their expression levels in three tea tree varieties were validated by qRT-PCR.ResultIn this study, we measured the internode lengths of the three varieties and found that their internode lengths were ‘Feiyun’ > ‘Qiancha 1’ > ‘Longjing 43’. 10,518 differentially expressed genes were identified through transcriptome sequencing and analysis. GO and KEGG enrichment showed that these differentially expressed genes were mainly enriched in plant hormone signal transduction and DNA-binding transcription factor activity pathways. WGCNA analysis identified two modules significantly correlated with internode length. Combining enrichment analysis with WGCNA results, 28 candidate genes associated with internode length were identified. In addition, it was found that the expression levels of DELLA and GA3ox were highly expressed in ‘Longjing 43’, while GA2ox, WRKY, and ERF were highly expressed in ‘Feiyun’, showing significant positive and negative correlations with internode length, respectively.DiscussionOur results provide candidate genes for studying the molecular mechanism of stem elongation, and provide a theoretical basis for selection machine harvested tea varieties and improvement of mechanical harvesting efficiency.